Thin-Film Transistors from Electrochemically Exfoliated In2Se3 Nanosheets - Xiangxiang Gao; Hai-Yang Liu; Jincheng Zhang; Jian Zhu; Jingjing Chang; Yue Hao (Micromachines, 2022)
The wafer-scale fabrication of two-dimensional (2D) semiconductor thin films is the key to the preparation of large-area electronic devices. Although chemical vapor deposition (CVD) solves this problem to a certain extent, complex processes are required to realize the transfer of thin films from the growth substrate to the device substrate, not to mention its harsh reaction conditions. The solution-based synthesis and assembly of 2D semiconductors could realize the large-scale preparation of 2D semiconductor thin films economically. In this work, indium selenide (In2Se3) nanosheets with uniform sizes and thicknesses were prepared by the electrochemical intercalation of quaternary ammonium ions into bulk crystals. Layer-by-layer (LbL) assembly was used to fabricate scalable and uniform In2Se3 thin films by coordinating In2Se3 with poly(diallyldimethylammonium chloride) (PDDA). Field-effect transistors (FETs) made from a single In2Se3 flake and In2Se3 thin films showed mobilities of 12.8 cm2·V−1·s−1 and 0.4 cm2·V−1·s−1, respectively, and on/off ratios of >103. The solution self-assembled In2Se3 thin films enriches the research on wafer-scale 2D semiconductor thin films for electronics and optoelectronics and has broad prospects in high-performance and large-area flexible electronics.